Althochdeutsche Aratorglossen - Tiefenbach, Heinrich (Vandenhoeck & Ruprecht, 1977)
Includes lists of the glosses.
Keywords: Arator; Glossen; Oudhoogduits; Deutsch; German language; Glosse; Althochdeutsch